PP.33 Uncovering the Complex Relationships Between Maternal Age, Antenatal Detection Rates, and Pregnancy Outcome in Cases of Down Syndrome. (26th April 2013) - Jordan, CF; Berry, LE; Budd, JLS; Mousa, HA; Draper, ES
Abstract : Background: Screening for Down Syndrome (DS) must be offered to all pregnant women in the UK, irrespective of age, between 10 +0 and 20 +0 weeks gestation. Current targets require antenatal detection rates between 75% and 90% of screened women. Aim: To use data from the East Midlands & South Yorkshire Congenital Anomaly Register (EMSYCAR) to explore the complex and changing relationships between antenatal diagnosis of DS, increasing maternal age and changing attitudes to termination over fifteen years. Methods: 1805 cases of DS were identified in 922, 216 births between 1998 and 2011, an overall prevalence of 19.57/10, 000. Cases were analysed by maternal age and pregnancy outcome, with mean gestational age at diagnosis calculated for each age group by cohort year. Results: 1025 DS cases (56.8%) were diagnosed antenatally, with the mean gestational age at diagnosis decreasing from 32 weeks in 1998/2000 to 20 in 2009/11. However, 49.1% (C.I. 42.1, 56.0) of DS cases in mothers under 25 were diagnosed antenatally, compared with 62.5% (C.I. 59.4, 65.6) for mothers over 35. While termination rates fell over time, they also differed significantly between age groups. 67.0% (C.I. 57.0, 75.9) of mothers <25 terminated an affected pregnancy compared with 83.7% (C.I. 80.5, 86.5) of those aged >34. Termination rates over time fell more abruptly among the youngest mothers. Conclusion: Despite known variation in birth prevalence of DS with maternal age, more research is needed to determine the role of maternal age in choices concerning screening uptake, consequent antenatal detection and subsequent decisions affecting pregnancy outcome.